Implementation of Indah Mayang Embroidery in Pariaman City to Increase Sales of the Creative Fashion Industry - Irja, Irja; Rahmat, Fadri; Febrianty, Syielvi Dwi; Surya, Wirma (Universitas Negeri Medan, 2023)
The creative economy is a new era of economic concepts that prioritizes information and creativity and relies on human resources' ideas as the primary production factor in economic activities. Pariaman City's traditional embroidered cloth business is one of the creative industries of the fashion sub-sector. The Embroidery Naras fabric business in Kota Pariaman has seen a drastic decrease in sales turnover since the Covid-19 pandemic, so entrepreneurs are looking for alternative solutions to increase their sales again. This research aims to find solutions to the problems faced by embroidered fabric craftsmanship, specifically how to increase sales volume after the covid-19 pandemic by advancing the creative embroidered fashion industry through the role of increasing production, creativity, and innovation. There are two types of data used: primary data and secondary data. Data collection, data reduction, data presentation, and conclusions are the data analysis techniques used in this study. According to the findings, increasing production played only a 33% role. This demonstrates that craftsmen play a smaller role in increasing production to 100%. While the criteria for increasing creativity reaches 70%, it demonstrates that it plays an important role in increasing sales volume. It reaches 15% for the global marketing criteria, indicating that it does not play a role in global marketing, and it reaches only 3% for the use of technology, indicating that it does not play a role in the production process. Similarly, increasing revenue by 33%, As a result, it plays a smaller role in increasing revenue through direct and online sales.